An Updated Scoping Review of Factors Associated with Length of Stay in Emergency Department - Kurhayati K; Emaliyawati E; Trisyani Y (Journal of Multidisciplinary Healthcare, 2025)
Kurhayati Kurhayati,1 Etika Emaliyawati,2 Yanny Trisyani2 1Postgraduate Nursing Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Emergency and Critical Care Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, IndonesiaCorrespondence: Yanny Trisyani, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Fax +620227795596, Email yanny.trisyani@unpad.ac.idBackground: The Emergency Department (ED) is important to the hospital healthcare system. However, increasing patient visits to the ED have increased the length of stay (LOS), which contributes to overcrowding, resource constraints, and decreased quality of care. Factors affecting LOS are complex and involve patient characteristics, hospital operations, and health system policies.Purpose: This review aimed to explore the factors influencing ED LOS.Methods: This study employed a scoping review with the PRISMA-ScR approach, analyzing articles from PubMed, Scopus, Taylor & Francis, and EBSCOhost databases published between 2022 and 2025. The keywords used were Emergency department patients OR ED patients OR Hospital admissions OR Emergency visits AND Length of stay OR hospital stay AND Predictor OR Factor. The quality appraisal of the articles was assessed using the Joanna Briggs Institute critical evaluation tool. Data were analyzed using descriptive qualitative and thematic analysis.Results: Factors influencing LOS in the ED were categorized into five main categories: (1) Patient characteristics (advanced age, male gender, comorbidities, and specific clinical conditions such as sepsis and blood diseases); (2) Time and environmental factors (nighttime, weekend, and winter visits); (3) Hospital and health system factors (hospital type, bed capacity, insurance status, and triage severity); (4) Diagnostic and treatment processes (waiting times for radiology and laboratory examinations, delays in specialist consultations, and limited inpatient beds); and (5) Patient arrival mode (arriving by ambulance or referred from another hospital).Conclusion: Longer LOS in the ED is influenced by various multidimensional factors that interact with each other. To reduce patient stays in the ED, efforts to optimize triage, improve diagnostic efficiency, and strengthen coordination between hospital units are needed. Evidence-based strategies such as digitizing medical records and predictive analytics can help improve service efficiency and reduce ED congestion.Keywords: emergency department, length of stay, overcrowding, predictors, service efficiency